Financial Outcomes of Total Quality Management in Enhancing Environmental Performance through Green Manufacturing Practices - Cahyono, Tomy Dwi; Suarantalla, Ryan; Fahira, Jihan (Jurnal Ilmiah Raflesia Akuntansi, 2023)
The adoption of Total Quality Management (TQM) practices has been recognized as a key strategy for improving organizational performance, particularly in enhancing environmental outcomes. This study aims to analyze the financial outcomes of TQM in improving environmental performance through the mediation of green manufacturing practices. The research uses a quantitative approach, with a sample drawn from manufacturing companies in Indonesia. The data were collected through surveys distributed to 150 respondents, including plant managers, environmental managers, and production supervisors. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the direct and indirect relationships among TQM, green manufacturing, environmental performance, and financial outcomes. The results indicate that TQM practices significantly improve environmental performance, and green manufacturing practices mediate this relationship, leading to positive financial outcomes. Specifically, the study finds that companies with higher TQM implementation experience reduced operational costs, improved energy efficiency, and enhanced product quality, which translate into increased profitability and financial stability. This study contributes to understanding the financial benefits of integrating quality management and sustainability practices, providing valuable insights for companies seeking to enhance their environmental and financial performance simultaneously.